The Effects of Eccentric and Concentric Exercise on Carbohydrate Metabolism - Oikonomou, Δημήτριος; Sakellariou, Γιώργος; Theodorou, Αναστάσιος; Paschalis, Βασίλης; Nikolaidis, Μιχάλης; Jamurtas, Αθανάσιος (Inquiries in Physical Education and Sport, 2015)
The main aim of this review is to present the effects of eccentric and concentric exercise on carbohydrate metabolism in animals and humans. We reviewed studies that employed the three most frequently used protocols to compare eccentric with concentric contractions: eccentric and concentric contractions on an isokinetic dynamometer, downhill anduphill running and electrical stimulation. Concentric exercise appeared to diminish muscle glycogen to a greater extent compared to eccentric exercise whereas eccentric exercise induced a lower rate of glycogen replenishment, a lower activation of glycogen synthase activity, a greater decrease in GLUT 4 protein content and a higher increase in insulin resistance. The main mechanism for this great metabolic stress observed after eccentric contractions might be related to the greater and prolonged muscle damage that this type of exercise induces. Muscle-damaging exercise has been related to prolonged myofibrillar disruption and prolonged inflammation – sarcolemma damage, whereas this might impair the functionality of the muscle cell. Therefore, it seems that there might be a connection between the muscle damage and the metabolic impact eccentric exercise provokes. In conclusion, the main finding of the present review is that muscle-damage caused by eccentric exercise might constitute the mechanism for the observed metabolic effects on carbohydrate metabolism. We propose that eccentric exercise should be viewed as a different challenge compared to concentric exercise with regard to its impact on muscle damage and its effect on carbohydrate metabolism.